Tinjauan Laki-Laki Feminin Perspektif Regulasi Penyiaran Indonesia dan Sosial Budaya Dalam Moderasi Islam - Muhammad Husni Ritonga (IAIN Padangsidimpuan, 2019)
Feminine male behavior is the behavior of a man imitating a person’s feminity. For some people, this behavior is a natural thing in the world of entertainment, but for others it is a matter that violates the normative. It is often performed by the actors who play a role in a television broadcast program, the implications of such behavior in fact inconsistent with the values or religion, culture, and age restictions. However, regulation of such behavior of considered weak because it does not specify the prohibition of such behavior. On the hand, this regulations become something protected, there will be the possibility of some people who give propaganda against male behavior feminine through broadcast media. Result found first, that the feminine male behavior is not accordance with norms of religion, and culture. Second, the absence of regulation significantly explain the behavior of men who resemble women in the Code of Conduct of Broadcast (P3) and the Broadcast Program Standards (SPS) 2012. Third, the link with the socio-cultural behavior is deliberately displayed on the broadcast program to destabilize heterosexual normative view.